2011
DOI: 10.1159/000330213
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn about Autism from Studying Fragile X Syndrome?

Abstract: Despite early controversy, it is now accepted that a substantial proportion of children with fragile X syndrome (FXS) meets diagnostic criteria for autism spectrum disorder (ASD). This change has led to an increased interest in studying the association of FXS and ASD because of the clinical consequences of their co-occurrence and the implications for a better understanding of ASD in the general population. Here, we review the current knowledge on the behavioral, neurobiological (i.e., neuroimaging), and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 305 publications
3
140
0
1
Order By: Relevance
“…On the other hand, concurrent Autism Spectrum Disorder occurs in 15-60% of Fra X cases and because of such high prevalence, screening for FMR1 mutation is highly recommended in autistic children. Interestingly, psychosis and catatonia have been reported in permutation carriers where multiple genetic and environmental hits resulted in intensified involvement and significant clinical expression [21,23,24].…”
Section: Journal Of Child and Adolescent Behaviormentioning
confidence: 99%
“…On the other hand, concurrent Autism Spectrum Disorder occurs in 15-60% of Fra X cases and because of such high prevalence, screening for FMR1 mutation is highly recommended in autistic children. Interestingly, psychosis and catatonia have been reported in permutation carriers where multiple genetic and environmental hits resulted in intensified involvement and significant clinical expression [21,23,24].…”
Section: Journal Of Child and Adolescent Behaviormentioning
confidence: 99%
“…In some studies, the severity of sleep problem was reported in children with autism and these children have a higher prevalence of sleep disorder than typically developing children [50][51][52]. And ASD with sleep problems have commonly showed the overactive and stereotypic behavior.…”
Section: Sleep Problems In Individuals With Autistic Fxsmentioning
confidence: 99%
“…Hence, neurobehavioral features of FXS consist of a wide range of variable cognitive and language impairments as well as associated neurobehavioral problems (i.e., attention difficulties, hyperactivity, anxiety, and autistic features) [14,10]. Together, they constitute the major medical and educational concerns for patients with FXS.…”
Section: Neurobehavioral Features In Fxsmentioning
confidence: 99%
“…Therefore, FXS is often "detected" after atypical behaviors and delays in skill acquisition begin to emerge [23,24]. As noted above, recent advances in understanding of the mutations of the FMR1 gene have enabled not only a model for neurodegeneration, but also more widely recognized the model for ASD [10,25].…”
Section: Neurobehavioral Features In Fxsmentioning
confidence: 99%
See 1 more Smart Citation